2019
DOI: 10.1038/s41598-019-48159-4
|View full text |Cite
|
Sign up to set email alerts
|

Strip rotary tillage with a two-year subsoiling interval enhances root growth and yield in wheat

Abstract: Excessive tillage and soil compaction threaten the sustainable farmlands in the Huang-Huai-Hai Plains of China. Our study explores tillage practices to improve soil and root ecology and promote productivity in the winter wheat fields. We tested the impact of plowing, rotary, strip rotary tillage and strip rotary tillage with a two-year subsoiling interval (SRS) on wheat yield and root quality. SRS decreased soil bulk density compared with other treatments, resulting in lower soil penetration resistance. Root m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 46 publications
(62 reference statements)
1
20
0
Order By: Relevance
“…The authors' previous studies found that replacing reduced, ploughless tillage and row sowing with ST-OP increased the winter barley yield by 6.4-7.7% [45], and the winter wheat yield by 6.1-10.4% [46]. The results of studies by other authors also show that strip-till may increase wheat yields as compared to other cultivation methods [47,48]. The high cereal yields may derive from the beneficial effect that strip-tillage has on soil properties, a border effect, and the microclimate in the canopy.…”
Section: Discussionmentioning
confidence: 93%
“…The authors' previous studies found that replacing reduced, ploughless tillage and row sowing with ST-OP increased the winter barley yield by 6.4-7.7% [45], and the winter wheat yield by 6.1-10.4% [46]. The results of studies by other authors also show that strip-till may increase wheat yields as compared to other cultivation methods [47,48]. The high cereal yields may derive from the beneficial effect that strip-tillage has on soil properties, a border effect, and the microclimate in the canopy.…”
Section: Discussionmentioning
confidence: 93%
“…Winter wheat and forage legumes, as well as other plants and soil microorganisms, compete for soil nitrogen. Applying no-tillage or reduced tillage methods increases soil density, and reduces aeration and water supply [ 41 ], resulting in the slow mineralization of plant residues.…”
Section: Discussionmentioning
confidence: 99%
“…By reducing tillage intensity, nitrogen is released at later stages of crop growth during the growing season [ 21 , 47 ]. In addition, the development and depth of penetration of the main crop roots is also determined by tillage [ 41 ]. Our studies (Assessment 3) showed that in most cases higher N-NO 3 levels remained after ploughing-in forage legumes.…”
Section: Discussionmentioning
confidence: 99%
“…Root samples were collected and refrigerated at −80 • C. Half of the root samples were used to measure root length, root surface area, and root diameter measurements using an Epson V700 scanner (Seiko Epson Corp., Japan) and WinRHIZO 2013 software (Regent Instruments Canada Inc., Canada). Root length density and root surface area density were calculated according to He et al (2019). The remaining root samples were used for the measurements of root malondialdehyde (MDA) concentration, superoxide dismutase (SOD) activity, and root activity.…”
Section: Root Morphology Characteristics and Biochemical Assaysmentioning
confidence: 99%